2019
DOI: 10.3389/fchem.2019.00226
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Organic Light Emitting Diodes Using Solution-Processed Alkali Metal Carbonate Doped ZnO as Electron Injection Layer

Abstract: In this study, we demonstrate highly efficient, inverted organic light-emitting diodes (IOLEDs) using solution-processed alkali metal carbonate doped ZnO as an electron injection layer (EIL) and tris-(8-hydroxyquinoline) aluminum (Alq 3 ) as an emitter layer. In order to enhance the electron injection efficiency of the IOLEDs, the ZnO EIL layers were modified by doping various alkali metal carbonate materials, including Li 2 CO 3 , Na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…This is within the standard value of 23.0 eV for Zn 2+ 62 . A similar value (23.00 eV) has been reported previously 63 for ZnO nanoparticles, though obtained with different synthetic methods. This result confirms that the Zn exists mostly as Zn 2+ surrounded by the O 2− oxidation state in the hexagonal wurtzite ZnO form.…”
Section: Resultssupporting
confidence: 91%
“…This is within the standard value of 23.0 eV for Zn 2+ 62 . A similar value (23.00 eV) has been reported previously 63 for ZnO nanoparticles, though obtained with different synthetic methods. This result confirms that the Zn exists mostly as Zn 2+ surrounded by the O 2− oxidation state in the hexagonal wurtzite ZnO form.…”
Section: Resultssupporting
confidence: 91%
“…For a single-layer OLED, efficient charge injection via ohmic contacts is a crucial prerequisite, since blocking layers are absent 9 . For an inverted OLED, a low work function transparent bottom electrode is thus required 15 . Several attractive options for such bottom electrodes have been published, among which is a ZnO electrode with a thin polyethyleneimine layer to reduce the work function down to 3.1 eV 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the variation of the carbonate source may exert a significant influence on the dehydrofluorination reactions and thus the final properties of activated carbon, because of the distinct properties of the carbonates caused by the difference in the cations. For instance, it has been reported that ZnO films doped with various alkaline metal carbonates showed quite different electron mobilities and work functions, which could lead to different electron injection properties of these devices and differences in the device performance. , Moreover, the incorporation of ion-rich materials in the composite can provide faster ion transport when the composite is charged . In particular, smaller ions can easily disperse to be adsorbed in the nanopores of AC and contribute to increasing the charging and discharging rates of the electrode.…”
Section: Introductionmentioning
confidence: 99%